2017
DOI: 10.1007/s10479-017-2542-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying sustainable control of inventory systems with non-linear backorder costs

Abstract: Traditionally, when optimizing base-stock levels in spare parts inventory systems, it is common to base the decisions either on a linear shortage cost or on a certain target fill rate. However, in many practical settings the shortage cost is a non-linear function of the customer waiting time. In particular, there may exist contracts between the spare parts provider and the customer, where the provider is obliged to pay a fixed penalty fee if the spare part is not delivered within a certain time window. We cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several studies on structure of emergency supply chain (Alessandra 2012; Balcik et al 2010;Balcik and Beamon 2008;Beamon and Balcik 2008;Dubey et al 2017b) postulated that lack of experience and the incompetence of employees of different organizations are the root cause of ineffi-ciency. Studies analyzing inventory management (Chen et al 2017;Johansson and Olsson 2017;Taleizadeh 2018) have also denoted that inappropriate and inadequate allocation of resources and its mismanagement are the key inhibiting forces in achieving operational success. The authors Park et al (2013) have analyzed the emergency supply chain management of Japan and revealed that the absence of effective organizational structure is a burning issue in the balanced operation of emergency supply chain management during a disaster.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on structure of emergency supply chain (Alessandra 2012; Balcik et al 2010;Balcik and Beamon 2008;Beamon and Balcik 2008;Dubey et al 2017b) postulated that lack of experience and the incompetence of employees of different organizations are the root cause of ineffi-ciency. Studies analyzing inventory management (Chen et al 2017;Johansson and Olsson 2017;Taleizadeh 2018) have also denoted that inappropriate and inadequate allocation of resources and its mismanagement are the key inhibiting forces in achieving operational success. The authors Park et al (2013) have analyzed the emergency supply chain management of Japan and revealed that the absence of effective organizational structure is a burning issue in the balanced operation of emergency supply chain management during a disaster.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, the demand of each part type was known per period and the backorder was considered in the cell formation problem. Johansson and Olsson (2017) presented a spare parts inventory control under two different backorder structures including piecewise constant backorder costs and general non-linear backorder costs. It was assumed that backorders at the sites and at the central warehouse were satisfied according to the first come-first served rule (FCFS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic has highlighted the need for humanitarian action to overcome the critical situation of vulnerable populations, inter alia (de Camargo Fiorini et al, forthcoming;Queiroz et al, 2020) and has underlined the importance of having appropriate resources and planning in place to deal with the pandemic. The appropriate allocation and management of resources is sine qua non to achieving operational success (Chen et al, 2017;Johansson & Olsson, 2017;Taleizadeh, 2018). Dolgui et al (2018) argue for the appropriate allocation of limited resources in those circumstances where disasters lead to humanitarian challenges and industrial crises to balance both human life rescue and industrial sector recovery.…”
Section: Introductionmentioning
confidence: 99%